Synthesis of Tungsten Oxide Nanowires onto ITO Glass Using T-CVD - Abuzairi, Tomy; Huang, Bohr-Ran; Lin, Tzu-Ching (Makara Journal of Technology, 2013)
Tungsten oxide is an n-type semiconductor with interesting physical and chemical properties that make it suitable for various technological applications. Tungsten oxide nanowires were synthesized not only at low temperature but also without the use of any catalysts. The tungsten oxide nanowires were synthesized at 550 °C with tungsten layers onto the ITO glass using thermal chemical vapor deposition (T-CVD). The SEM image shows that the tungsten oxide nanowires are effectively grown with the 200 nm tungsten film. The Raman spectra shoulder at ~690 cm-1 proves the synthesized of tungsten oxide nanowires.